A construção e a implementação de uma ferramenta de gestão da informação para projetos de assistência técnica e extensão rural - o Sistema Integrado de Gestão Rural (SIGRA) - Friedrich, Gustavo do Nascimento (2022)
In this research, the process of implementation and development of SIGRA (Integrated Rural Management System of ATER/ATES) used within the scope of the Technical, Social and Environmental Advisory Program (ATES) was analyzed and described. The ATES program is a service created by INCRA with the aim of providing comprehensive and continuous technical, social and environmental advice to families settled by agrarian reform. Its purpose is to advise families on economic, social and environmental aspects, in order to improve the families' quality of life, improve batch management, production, processing and marketing, in addition to other issues such as well-being, health, education, basic sanitation, gender, youth, environmental preservation, etc. SIGRA emerged in Rio Grande do Sul as a result of a combination of efforts in the search for a model for organizing ATES services for Settlement Projects. A tool was needed that would allow effective interaction between the state context and the local reality. And that it also met the expectations and aspirations of the settled families and was in accordance with INCRA guidelines. SIGRA's main characteristics are: being an agile system, capable of organizing and managing the main information on the reality of agrarian reform settlements in Rio Grande do Sul; to assist in the elaboration of public policies and in the proposition of actions that contribute to the development of the settlements; make available to the settled families and their organizations qualified information that can help in the planning of the activities developed in the production unit, as well as, contribute to the discussions and claims before the local and regional entities and INCRA itself; and, to be an instrument that helps the technical teams in the process of organization, planning and monitoring of the work, through the generation and analysis of information related to the environmental, social and productive dynamics of the settlements. From SIGRA, other applications derived from this experience emerged, such as SIGRA TCU/CGU, Rice Farming Project Form, Municipal/Cooperatives SIGRA, Quilombola Information System (SIQ) and National Occupational Supervision System (SNSO).